Integrating Ethnomathematics with Project-Based Learning: Student Perceptions on the Development of Mathematical Critical Thinking Skills in Geometry - Syaripah Syaripah; Arza Lia Citra; Tasha Marshanda; Delvi S Margaretha; Nina Malinda; Enjelly W Wulandari (STAI Hubbulwathan Duri, 2025)
Mathematical critical thinking is a vital higher-order cognitive skill emphasized in higher education curricula. Project-Based Learning (PjBL) promotes this skill by encouraging collaboration, communication, problem-solving, and independent thinking. When combined with ethnomathematics—a culturally responsive approach that integrates students’ heritage and real-life contexts—PjBL can potentially enhance student engagement and deepen mathematical understanding. This study explored students’ perceptions of PjBL integrated with an ethnomathematics approach in a transformation of geometry course. A quantitative descriptive design was employed, involving purposive sampling of twelve students. Data were collected through a closed-ended questionnaire, using a five-point Likert scale to measure perceptions of both skill development and instructional appropriateness. Findings revealed that students rated the development of their critical thinking skills with a mean score of 4.85 (Good). Additionally, the use of PjBL with an ethnomathematics approach was perceived as highly appropriate for the course, with a mean score of 5.00 (Very Good). The results suggest that integrating PjBL with ethnomathematics can effectively foster mathematical critical thinking. This approach not only creates interactive learning environments but also increases students' motivation by connecting mathematical concepts to their cultural and practical experiences. PjBL combined with ethnomathematics offers a promising pedagogical strategy for enhancing critical thinking in mathematics education. It supports active learning and cultural relevance, enriching both cognitive and motivational aspects of student learning.